2004
DOI: 10.1097/01.sla.0000129358.80798.62
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Morbidity of Axillary Lymph Node Dissection and the Sentinel Lymph Node Technique

Abstract: Our data indicate that a complete AXLND can be performed with minimal long-term morbidity. The lower the morbidity of AXLND, the less acceptable are the unique complications of the SLN technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
16

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 20 publications
0
26
0
16
Order By: Relevance
“…Although it is clear that ALND provides no therapeutic benefit to patients with histologically negative nodes and exposes patients to significant potential morbidity, some have advocated ALND as the optimum surgical procedure which is the ''gold standard'' for staging the axilla [16]. These concerns have been raised by the finding of false negative rates of 5-10% for SNB when followed by axillary dissection, and have caused some to question its appropriateness in patients at high risk for axillary nodal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is clear that ALND provides no therapeutic benefit to patients with histologically negative nodes and exposes patients to significant potential morbidity, some have advocated ALND as the optimum surgical procedure which is the ''gold standard'' for staging the axilla [16]. These concerns have been raised by the finding of false negative rates of 5-10% for SNB when followed by axillary dissection, and have caused some to question its appropriateness in patients at high risk for axillary nodal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The SN biopsy has therefore reduced the morbidity associated with axillary lymph node dissection (ALND) and has readily evolved into the standardized staging procedure in clinically node negative breast cancer patients (Veronesi et al 1999;Golshan et al 2003;Lyman et al 2005;Ferrari et al 2006). For instance, previous studies demonstrated that morbidity of ALND including lymphedema, arm paresthesia, chronic pain and immobility occurs in 5% to 50% of the patients (Kuehn et al 2000;Petrek et al 2001;Silberman et al 2004;Wilke et al 2006). In addition, SN biopsy is an acceptable procedure alterative to ALND for staging the axillary lymph node status in patients with early stage breast cancer (Lyman et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…14 In contrast to this research, current reports of incidence with SNLB has been 0 -23%. 5,10,12 ALND 5,15,18,21,22,[23][24][25][26] and radiotherapy 8,14,25,27,28 are thought to be contributing factors for SLE. However, lack of consensus occurs regarding which risk factors contribute consistently to SLE.…”
mentioning
confidence: 99%
“…However, lack of consensus occurs regarding which risk factors contribute consistently to SLE. 8,14,24 Other factors that may increase the risk for developing SLE are body mass index (BMI), 14,29,30 dominant arm, 31,32 age, 33 weight gain/obesity, 5,11,13,29,33 staging, 10,34 number of lymph nodes removed, 29 medical therapies, 35,36 and infection. 10,13 …”
mentioning
confidence: 99%